Simulation of Online Learning Interaction Relation Network Based on BA Model (International Conference on Computers in Education, 2019)
To explore the knowledge dissemination in online learning interaction, the online learning interaction relation network should be constructed firstly. However, the random network, small-world network and scale-free network proposed in the current research can not describe the interactive relationship of online learning interaction. Therefore, how to build the online learning interaction relation network has become a fundamental research problem to be solved. This study updates the BA model algorithm to construct a simulated interaction relation network of online learning. The graphs of degree distribution show that the interaction relation network simulated in this study conforms to the actual rule of online learning interaction of instructors and learners.